A Systematic Review of Tourism Governance: Sustainable Tourism Governance Model Post COVID-19 - Aqil Teguh Fathani; Novia Amirah Azmi; Eko Priyo Purnomo; Sukanya Aimim Tham; Rohana Ahmad (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
This study aims to examine and categorise themes and concepts related to the study of tourism sustainability governance during the COVID-19 pandemic. The study of tourism governance is becoming a big topic since the emergence of COVID-19, especially from the management point of view, the role and contribution of policy actors, the economy, and changes in social structures. Through qualitative and quantitative analysis with the help of software, VOSviewer and NVivo12+ obtained 78 Scopus-indexed articles relevant to the study. The articles were collected from various publishers, namely Elsevier, SAGE, MDPI, and Taylor and Francis. The results showed 71 concepts in the study of tourism governance, which the researchers categorised into 6 clusters-related to the discussion of the dominant themes, namely tourism development, economic recession, world change, ecology, and policy. The significance of this research is the discovery of the concept of sustainable tourism governance during the COVID-19 pandemic, which can assist in developing a conceptual framework for future studies related to the tourism sector. While the limitations of this study are reviewed are only articles obtained from the Scopus database, there is no comparison. Therefore, it is necessary to use a comparative approach involving the Scopus database and Web of Science (WoS) for further research